2019
DOI: 10.17219/acem/110326
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dantrolene and methylprednisolone against spinal cord injury-induced early oxidative damage in rabbit bladder: A comparative experimental study

Abstract: Background. Spinal cord injury (SCI) may cause dysfunction in the bladder and many distal organs due to systemic inflammatory response and oxidative stress-related injury. Objectives. We investigated the preventive effects of dantrolene (DNT) and methylprednisolone (MP) on stress-induced tissue damage in rabbit bladder with SCI. Material and methods. A total of 35 rabbits were included in this study and they were divided into 5 groups: group 1-control, group 2-SCI only, group 3-SCI and DNT, group 4-SCI and MP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This is manifested by the significant suppression of NO, TNF-α, IL-6, and MDA levels in contrast to elevated SOD activity. In line with the findings of this study, several reports recorded significant declines in TNF-α, IL-6 [ 67 , 68 ], and NO [ 69 ] with an enhanced antioxidant capacity [ 70 , 71 ] upon treating acute SCI with MPSS. Furthermore, the PD results agreed with previous studies by Liu et al [ 72 ], Ni et al [ 73 ], and Chen et al [ 74 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is manifested by the significant suppression of NO, TNF-α, IL-6, and MDA levels in contrast to elevated SOD activity. In line with the findings of this study, several reports recorded significant declines in TNF-α, IL-6 [ 67 , 68 ], and NO [ 69 ] with an enhanced antioxidant capacity [ 70 , 71 ] upon treating acute SCI with MPSS. Furthermore, the PD results agreed with previous studies by Liu et al [ 72 ], Ni et al [ 73 ], and Chen et al [ 74 ].…”
Section: Discussionsupporting
confidence: 90%
“…Methylprednisolone (MP) is a glucocorticoid drug that has been used in the clinical treatment of SCI due to its highly effective antiinflammatory properties (Hall and Braughler, 1981). Studies have demonstrated that MP has neuro-protective properties against SCI by inhibiting microglia/macrophage accumulation, reducing calcium influx, increasing blood flow, and protecting glia from dysmetabolic insults (Tang et al, 2015;Keles et al, 2019;Samano and Nistri, 2019).…”
Section: Introductionmentioning
confidence: 99%